Work Motivation and Employee Performance at the Department of Manpower Office in Makassar City - Andi Winda Aksari Hamzah; Muhammad Nur Yamin (Universitas Negeri Makassar, 2023)
This research aims to determine the work motivation and performance of employees at the Makassar City Manpower Office. This study is a descriptive research with a quantitative approach. The data collection techniques used in this research are observation, questionnaire/survey, and documentation. The data analysis techniques used are descriptive statistical analysis and inferential statistical analysis. The results of this research indicate that the work motivation at the Makassar City Manpower Office is categorized as good based on the indicators of achievement needs, affiliation needs, and power needs. The employee performance at the Makassar City Manpower Office is categorized as very good based on the indicators of quality, quantity, work time, and cooperation. The results of the analysis and hypothesis testing show that there is a positive and significant influence between work motivation and employee performance. Based on the results of the determination analysis, the magnitude of the contribution given by the work motivation variable is 6.7 to employee performance at the Makassar City Manpower Office.